Experimental investigation of parallel restrainers effects on buckling-restrained thin steel plate shear walls. Issue 6 (2nd November 2021) - Aminifar, Farzin; Sheidaii, Mohammad Reza; Tariverdilo, Saeed
ABSTRACT: A novel, simple to apply, and economic buckling restrainer system is introduced for steel plate shear walls. The shear wall panel is restrained by parallel non-welded channel restrainers, which are installed on both sides of the steel panel. A set of experiments were designed to examine improvement in the seismic performance of the shear wall due to the application of the proposed restrainer system. Three 1/4-scale down single-story single-bay steel panel specimens including one panel without and two panels with different number of restainers are subjected to cyclic loading. The behavior of steel panel with and without the restrainers is assessed in terms of initial stiffness, ultimate loading capacity, stiffness/strength degradation, and energy dissipation capacity. The use of the proposed restrainer system significantly improves the energy dissipation capacity of the shear wall and this enhancement is increasing at larger drifts. Employing the proposed restrainer system, there is only a slight increase in the ultimate loading capacity, and at the same time, a significant increase in the initial stiffness of the shear wall. No strength degradation is observed for the range of the drifts up to 5%. A design recommendation for the sizing of the parallel restrainer components is also included.